Envelope modulational instability in the nonlinear dissipative transmission line - Kengne, E. (Нелінійні коливання, 2002)
Biinductance LC circuit is considered and envelope modulation is reduced to the complex nonlinear Schrodinger (CNLS) equation. The Benjamin ¨ – Feir (or modulational, as it is sometimes called) instability for the CNLS equation is investigated and reduced to the Lange – Newell criterion. Розглядається LC-ланцюг, для якого модуляцiя обвiдної зводиться до комплексного нелiнiйного рiвняння Шредiнгера (КНРШ). Вивчається нестiйкiсть за Бенджамiном та Фейєром (що iнодi називається модуляцiйною) для КНРШ i зводиться до критерiю Ланга – Ньювелла.